Comparison Between a Thermosiphon and a Wick Heat Pipe Performance with Temperature Difference - Fazri Amir; Samsul Rizal; Razali Thaib; Hamdani Umar; Nasruddin A Abdullah (Jurnal POLIMESIN, 2023)
The heat pipe (HP) is a fundamental heat transfer component frequently utilized for energy recovery in heating, ventilation, and air conditioning (HVAC). However, a heat pipe transmits heat from the hot side (evaporator) to the cold side (condenser), resulting in a temperature difference on both sides. There are numerous methods for measuring heat pipe performance. Using the temperature difference between the evaporator and condenser, the performance characteristics may be evaluated. The objective of this study is to compare the thermal performance of thermosiphon and commercial wick heat pipes (WHP) utilizing water as the working fluid and varying temperatures between the evaporator and condenser. The copper thermosiphon and commercial wick heat pipe had a diameter of 10 mm, a length of 800 mm, and a vacuum pressure of 5000 Pa. The filling ratios range between 30% and 50%, and it was evacuated at a pressure of 5000 Pa; the hot water temperatures at the evaporator were 30, 50, 70, and 90 ºC. Temperature was steadily increased every 30 minutes, and variations were observed at multiple places, including hot water, evaporator, and condenser wall. The average difference in temperature between the WHP and thermosiphon was around 0.6 degrees Celsius. The decreased temperature difference (T) indicates that the heat pipe is performing well. In addition, if the temperature difference is very great, the HP will dry up, therefore the WHP performs better than the thermosiphon.